DOES BOARD STRUCTURE AND OWNERSHIP STRUCTURE INFLUENCE THE PERFORMANCE OF LISTED COMPANIES: EVIDENCE FROM PHARMACEUTICALS AND CHEMICAL INDUSTRY OF BANGLADESH? - Chakraborty, Brishti (Copernican Journal of Finance & Accounting, 2023)
This study examines the influence of board structure and ownership structure on a firm’s financial performance in the pharmaceutical and chemical industry of Bangladesh. The data of this study is based on all listed companies in the pharmaceuticals and chemical industry on Dhaka Stock Exchange. Data was collected from the annual reports of the concerned industry from 2015 to 2020. To examine the data, the study has applied descriptive analysis, correlation analysis, VIF test, and the twostage least squares (2SLS) estimator using Eviews software. Based on existing empirical studies, seven major attributes (board size, board independence, board gender, managerial ownership, institutional ownership, audit committee size, and frequency of audit committee meetings) have been selected to identify their influence on a firm’s performance. Findings from the study show that there is an insignificant negative relationship among board size, board gender, frequency of meetings, and the firm’s financial performance but a significant relationship with board independence, institutional ownership, and frequency of meetings. The study has proposed that board size can be smaller but should be representative. This study will contribute to the literature on corporate governance and profitability in an emerging economy like Bangladesh.